Nickel(II)‐Mediated Reversible Thiolate/Disulfide Conversion as a Mimic for a Key Step of the Catalytic Cycle of Methyl‐Coenzyme M Reductase. (30th March 2020) - Bhandari, Anirban; Mishra, Saikat; Maji, Ram Chandra; Kumar, Akhilesh; Olmstead, Marilyn M.; Patra, Apurba K.
Abstract: According to the well‐accepted mechanism, methyl‐coenzyme M reductase (MCR) involves Ni‐mediated thiolate‐to‐disulfide conversion that sustains its catalytic cycle of methane formation in the energy saving pathways of methanotrophic microbes. Model complexes that illustrate Ni‐ion mediated reversible thiolate/disulfide transformation are unknown. In this paper we report the synthesis, crystal structure, spectroscopic properties and redox interconversions of a set of Ni II complexes comprising a tridentate N2 S donor thiol and its analogous N4 S2 donor disulfide ligands. These complexes demonstrate reversible Ni II ‐thiolate/Ni II ‐disulfide (both bound and unbound disulfide‐S to Ni II ) transformations via thiyl and disulfide monoradical anions that resemble a primary step of MCR's catalytic cycle. Abstract : Thiolate/disulfide conversions are mediated by nickel complexes mimicking the key step in the catalytic cycle of methyl‐coenzyme M reductase. Cyclic voltammetry and EPR spectroscopic measurements reveal monoradical‐based reversible switching of Ni II ‐thiolate/Ni II ‐disulfide couples (see picture).